Tantangan Paradox of Plenty Pembangunan Daerah di Aceh Setelah Dua Dekade Otonomi Khusus - Hendy Setiawan (Ministry of Home Affairs, 2022)
Aceh as a region rich in natural resources is still trapped in the paradox of plenty phenomenon. This is ironic if you look at Aceh, which is the poorest region on the island of Sumatra and the welfare of its people is low. This is of course a stark contrast that natural resource wealth should be able to make Aceh more prosperous from various sides. Law No. 18 of 2001 concerning special autonomy for Aceh was basically born as an attempt by the government to bring Aceh out of Aceh from the paradox of plenty. This means that none other than the goal of these efforts is welfare for Aceh. This type of research uses a qualitative approach with library research methods. Meanwhile, the stages of this research consist of problem identification, literature search, research aims and objectives, data collection, data analysis and interpretation, and research reporting. The results showed that special autonomy was not able to bring Aceh out of the paradox of plenty phenomenon. This means that the goals of welfare by creating low poverty, high HDI, high IDI, and low unemployment still seem to have not been completed. In addition, the presence of special autonomy arrangements for Aceh turned out to give birth to new challenges in the field of governance. So far, the disbursement of special autonomy funds has not been able to be managed evenly so economic and social inequalities still occur in Aceh. There is a tendency that the implementation of Aceh's special autonomy for the past two decades has been exploited by certain politically related groups. The DOKA disbursement, which began in 2008 from the central government, has not been felt by the people of Aceh to this day. This finding is certainly a critical reflection for the government to evaluate this asymmetric arrangement in a comprehensive and sustainable manner for the welfare of Aceh.